Antifungal spectrum characterization and identification of strong volatile organic compounds produced by Bacillus pumilus TM-R. Issue 6 (June 2019) - Morita, Toshiyuki; Tanaka, Issei; Ryuda, Noriko; Ikari, Masao; Ueno, Daisuke; Someya, Takashi
Abstract: To obtain biocontrol agents for suppression of food-deteriorating fungi during storage of agricultural products, bacteria producing volatile organic compounds (VOCs) with strong antifungal activity were screened and isolated from various environmental samples. Among 136 bacterial isolates, strain TM-R showed the strongest and broadest antifungal activity. Based on physiological and genetical characterization, the bacterium was identified as Bacillus pumilus . The effects of VOCs produced by the bacterium, which was grown on four types of agar media (nutrient, Trypto-Soya, Luria–Bertani, and TM Enterprise), were examined against six species of fungi ( Alternaria alternata, Aspergillus niger, Cladosporium cladosporioides, Curvularia lunata, Fusarium oxysporum, and Penicillium italicum) in both small- and large-scale tests (plate and 12-L tests, respectively). In the plate test, the bacterium markedly suppressed the mycelial growth of five fungi ( Alternaria alternata, Cladosporium cladosporioides, Curvularia lunata, F. oxysporum, and P. italicum ) but promoted the growth of Aspergillus niger . In the 12-L test, the degree of growth inhibitiondecreased; however, the bacterium grown on TMEA still exhibited the strongest inhibition, especially against P. italicum (growth inhibition rate of 93%). Surprisingly, the growth of Aspergillus niger was promoted even more strongly (−36%) by the bacterium on TMEA than in the plate test (−9%). Twenty-two of 32 VOCs detected by GC-MS were identified using three databases (NIST 2011, AromaOffice, and AroChemBase). The species and concentration of detected VOCs differed greatly among growth media. To identify causative antifungal VOCs, we estimated the correlation between growth inhibition of P. italicum by the bacterium grown on each of the four media vs. the relative abundance of individual VOCs. As a result, four VOCs (methyl isobutyl ketone, ethanol, 5-methyl-2-heptanone, and S-(−)-2-methylbutylamine) were determined to be the predominant antifungal VOCs. To the best of our knowledge, this study is the first to specify causative antifungal VOCs using such an approach.